Signaling pathways associated with interleukins 12 and 23 and epigenetic mechanism of sequential-specific regulation of expression of related genes by miRNAs as molecular markers for assessing the potential of anti-cytokine therapies - Grabarek, Beniamin O.; Wcisło-Dziadecka, Dominika L.; Mazurek, Urszula (Przegląd dermatologiczny, 2019)
The molecular targeted therapy is focused on blocking the activity of specific cytokines and the signalling cascades they activate. In the treatment of psoriasis, this type of therapy is based on treatment with anti-tumor necrosis factor drugs, anti-IL-12/23, anti-IL-17, inhibitors of JAK kinases. Interleukins 12 and 23 interact with the receptors to trigger the JAK/STAT signalling pathway, the end products of which are other cytokines, e.g. tumour necrosis factor, IL-17, interferon g. These cytokines affect both IL-12/23 shaping their concentration profile, as well as trigger other signalling paths themselves. Gene expression is regulated by DNA methylation, miRNA molecules and histone protein modifications. The miRNA seems to be a promising model of a molecular marker system. Understanding the interrelationships between individual signalling pathways associated with IL-12 and IL-23 and the role of epigenetic mechanisms to regulate their expression is important for the development and implementation of new diagnostic-therapeutic schemes and the further development of personalized medicine.